Occurrence of Ochroconis and Verruconis Species in Clinical Specimens from the United States - Giraldo, Alejandra (J Clin Microbiol, 2014)
Ochroconis is a dematiaceous fungus able to infect immunocompetent people. Recently, the taxonomy of the genus has been reevaluated, and the most relevant species, Ochroconis gallopava, was transferred to the new genus Verruconis. Due to the important clinical implications of these fungi and based on the recent classification, it was of interest to know the spectra of Ochroconis and Verruconis species in clinical samples received in a reference laboratory in the United States. A set of 51 isolates was identified morphologically and molecularly based on sequence analyses of the nuclear ribosomal RNA (nrRNA), actin, and β-tubulin genes. Verruconis gallopava was the most common species (68.6%), followed by Ochroconis mirabilis (21.5%). One isolate of Ochroconis cordanae was found, being reported for the first time in a clinical setting. The most common anatomical site of isolation was the lower respiratory tract (58.8%), followed by superficial and deep tissues at similar frequencies (21.6 and 19.6%, respectively). Interestingly, three new species were found, which are Ochroconis olivacea and Ochroconis ramosa from clinical specimens and Ochroconis icarus of an environmental origin. The in vitro antifungal susceptibilities of eight antifungal drugs against the Ochroconis isolates revealed that terbinafine and micafungin were the most active drugs.